2010
DOI: 10.1186/1471-2296-11-89
|View full text |Cite
|
Sign up to set email alerts
|

Chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) in adults: a qualitative study of perspectives from professional practice

Abstract: BackgroundChronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) can cause profound and prolonged illness and disability, and poses significant problems of uncertainty for healthcare professionals in its diagnosis and management. The aim of this qualitative study was to explore the nature of professional 'best practice' in working with people with CFS/ME.MethodsThe views and experiences of health care practitioners (HCPs) were sought, who had been judged by people with CFS/ME themselves to have been parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 24 publications
4
49
0
Order By: Relevance
“…This conclusion is consistent with a number of studies that found that negative stereotyping acts as a barrier to successful support for the patient,51 52 leading to a ‘vicious spiral of alienation between doctor and patient’ 39…”
Section: Epistemic Injustice Leads To Patient Harmsupporting
confidence: 89%
“…This conclusion is consistent with a number of studies that found that negative stereotyping acts as a barrier to successful support for the patient,51 52 leading to a ‘vicious spiral of alienation between doctor and patient’ 39…”
Section: Epistemic Injustice Leads To Patient Harmsupporting
confidence: 89%
“…These problems are acknowledged by health care professionals as impacting on recovery [21]. Teenagers also describe the results of delay in diagnosis as 'a difficult time' characterised by a lack of information, understanding and awareness of their condition [22].…”
Section: Discussionmentioning
confidence: 99%
“…CFS imposes a huge burden on patients, carers and families (Horton et al, 2010, Nacul et al, 2011, Sabes-Figuera et al, 2010. In the UK, adults who attend NHS specialist CFS services have been ill for a median duration of 3 years, and half of those who were employed at the onset of their illness have ceased working (Collin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%